Sol: Image and Meaning of the Sun in Roman Art and Religion, Volume I - Hijmans, Steven E. (Religions in the Graeco-Roman World Series, 2024)
Hijmans demonstrates that a sophisticated analysis of images of Sol sheds an entirely new light on the role of the sun in Roman religion. This book includes a discussion of relevant theory and a number of case studies. This is part I of a two-part set.